PsycEXTRA Dataset 2011
DOI: 10.1037/e683152011-002
|View full text |Cite
|
Sign up to set email alerts
|

Friends with benefits: On the positive consequences of pet ownership

Abstract: Social support is critical for psychological and physical well-being, reflecting the centrality of belongingness in our lives. Human interactions often provide people with considerable social support, but can pets also fulfill one's social needs? Although there is correlational evidence that pets may help individuals facing significant life stressors, little is known about the well-being benefits of pets for everyday people. Study 1 found in a community sample that pet owners fared better on several well-being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 35 publications
5
71
0
2
Order By: Relevance
“…Likewise, they do not show that more socially disconnected owners have unusually or exceptionally high levels of anthropomorphic thinking. This is consistent with evidence from previous studies that pets may often subtly supplement rather than replace social and emotional support from other humans (McConnell et al 2011;Krause-Parello 2012).…”
Section: Social Connections With Other Adultssupporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, they do not show that more socially disconnected owners have unusually or exceptionally high levels of anthropomorphic thinking. This is consistent with evidence from previous studies that pets may often subtly supplement rather than replace social and emotional support from other humans (McConnell et al 2011;Krause-Parello 2012).…”
Section: Social Connections With Other Adultssupporting
confidence: 93%
“…Such research should also help to establish whether and to what degree these different types of anthropomorphic thinking can influence the well-being of the owner, including ameliorating subjective feelings of loneliness (e.g., see Krause-Parello 2012) and also the behavior and welfare of the pet itself (Bradshaw and Casey 2007;Vaughn et al 2009;Antonacopoulos and Pychyl 2010b;Chur-Hausen 2010;Bradshaw 2011;McConnell et al 2011;Himsworth and Rock 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have reported the benefits of pet dog, assistance dog and guide dog ownership (Friedmann 1995, Lane and others 1998, Refson and others 1999, Whitmarsh 2005, Guest and others 2006, McConnell and others 2011, Ramírez and others 2014). Guide dogs have been found not only to provide the benefit of enhanced physical well-being mobility and independence to their guide dog owner, but also social, spiritual and emotional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Much HAI research has focused primarily on pet owners with significant health challenges, rather than pet ownership by average people in everyday life [6]. It has also mainly considered adults; less is known about the role pets play in the lives and wellbeing of children, much of which is observational studies of child/pet interaction, or interviews with children about their attitudes and beliefs regarding animals [10].…”
Section: Introductionmentioning
confidence: 99%